A facile synthesis, structural morphology and fluorescent properties of cross-linked poly(cyclotriphosphazene-co-1, 3, 5-tri(4-hydroxyphenyl)benzene) hybrid copolymer microspheres. (23rd August 2016) - Dar, Sami Ullah; Ali, Shafqat; Hameed, Muhammad Usman; Zuhra, Zareen; Wu, Zhanpeng
Abstract : Tunable size synthesis of fluorescent active microspheres with proposed unique chemical structure. Abstract : The ever increasing growth and interest in the field of material science for the production of functionalized polymer microspheres with tunable size is of pivotal importance. This research describes the one pot method for the facile synthesis of fluorescent active poly[cyclotriphosphazene- co -1, 3, 5-tri(4-hydroxyphenyl)benzene] (PCTHB) microspheres with the desired structural morphology obtained by the reaction of 1, 3, 5-tri(4-hydroxyphenyl)benzene (HPB) with hexachlorocyclotriphosphazene (HCCP) through the precipitation polymerization. The sizes of the microspheres can be tuned by changing the amount of both the cross linkers in a calculated molar ratio. The mean diameter of the microspheres varies in the range of 0.5–1.1 μm. The morphology and structure of PCTHB microspheres were characterized by FT-IR, solid state 31 P NMR, SEM, EDX-mapping and TEM analyses. A mechanism for the preparation of PCTHB microspheres has been proposed, in which HPB plays a crucial role, as its presence gives the final desired shape to the microspheres. The concentration of HBP beyond 2 mM has produced irregular morphology of the microspheres. Room-temperature photoluminescence spectra of the PCTHB microspheres reveal a strong emission peak at 372 nm. These fluorescent polymer PCTHB microspheres can be developed with great ease as compared to those with the aid of quantum dots and dyes. Due to these superior properties and novelty of our synthesized material, it can be used as a potential biomaterial for several applications such as diagnostics, photocatalysis, biological imaging, organic or inorganic analysis, and light emitting diodes.